Steel sheet and method for producing steel sheet
By controlling the chemical composition and metal structure of the steel plate, especially the characteristics of the soft surface part, and combining with specific processes, high-strength steel plates with excellent bending properties and low bending anisotropy are prepared, which solves the bending and bending anisotropy of the high-strength steel plates in the automotive impact absorbing members in the prior art, and improves the freedom and impact absorption capacity of the member.
Patent Information
- Application Number
- CN202380085100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-15
- Filing Date
- 2023-12-13
- Publication Date
- 2025-07-22
AI Technical Summary
The existing high-strength steel plates require less bending anisotropy and higher bending in automotive impact absorbing members, especially the strength areas above 1180 MPa are not effectively covered, and the shape requirements of complex components are not met.
By controlling the chemical composition of the steel plate and the metal structure, especially the structural characteristics of the soft surface, including the control of Vickers hardness ratio, Taylor factor ratio and island-shaped hard phase, combined with hot rolling, cold rolling and annealing processes, steel plates with excellent bending properties and low bending anisotropy are prepared.
Excellent bending and small bending anisotropy in high-strength areas are achieved, and the degree of freedom and impact absorption capacity of the impact absorption member are improved.
Smart Images

Figure BDA0005443611830000191 
Figure BDA0005443611830000291 
Figure BDA0005443611830000301
Abstract
Description
Technical Field
[0001] The present invention relates to a steel sheet and a method for manufacturing the same.
[0002] This application claims priority based on Japanese Patent Application No. 2022-200340 filed on December 15, 2022, the content of which is incorporated herein by reference. Background Art
[0003] Regarding steel sheets for automobiles, in consideration of the global environment, in order to reduce the weight of the vehicle body and improve fuel efficiency, the demand for high-strength steel sheets with a thin thickness and excellent formability has increased significantly. Among steel sheets for automobiles, especially for high-strength steel sheets used in vehicle body frame components, high strength is also required, and furthermore, high formability for expanded applications is required.
[0004] In addition, since automotive components are formed by pressure or the like, even if they are high-strength, excellent formability (such as uniform elongation rate, bendability) is required.
[0005] As such a high-strength steel sheet, Patent Document 1 discloses a high-strength steel sheet having a plate thickness center portion and surface soft portions formed on one side or both sides of the plate thickness center portion. In the cross-section of the high-strength steel sheet, the metallographic structure of the plate thickness center portion includes, by area ratio, tempered martensite: 85% or more, one or more of ferrite, bainite, pearlite, and retained austenite: a total of less than 15%, and quenched martensite: less than 5%. The metallographic structure of the surface soft portion includes, by area ratio, ferrite: 65% or more, pearlite: 5% or more and less than 20%, one or more of tempered martensite, bainite, and retained austenite: a total of less than 10%, and quenched martensite: less than 5%. The thickness of each of the surface soft portions formed on one side or both sides exceeds 10 μm and is 15% or less of the plate thickness. The average interval between the pearlite in the surface soft portion is 3 μm or more. The Vickers hardness (Hc) of the plate thickness center portion and the Vickers hardness (Hs) of the surface soft portion satisfy 0.50 ≤ Hs / Hc ≤ 0.75.
[0006] In addition, in Patent Document 2, a technique for controlling the in-plane anisotropy of bendability of a steel sheet to a small level in addition to a high hole expansion ratio as workability is disclosed. Thereby, it is possible to pressure-form into a particularly strict shape, and the degree of freedom in cutting a sheet from the steel sheet can be improved.
[0007] Prior Art Documents
[0008] Patent Documents
[0009] Patent Document 1: International Publication No. 2020 / 196060
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 2015-145521 Summary of the Invention
[0011] Problems to be Solved by the Invention
[0012] In impact absorbing members of automobiles, from the viewpoint of energy absorption during collisions, steel sheets with a smaller bending anisotropy than the steel sheets described in Patent Documents 1 and 2 are required. In addition, in recent years, the shapes of automobile members have become more complex, and an increased degree of freedom in obtaining components is required. By reducing the bending anisotropy of the steel sheet, the steel sheet described in Patent Document 2 is preferable in terms of also increasing the degree of freedom in obtaining components, but it cannot cover the high-strength steel sheets required for impact absorbing members, such as strength regions of 1180 MPa or more.
[0013] The present invention has been made in view of the above circumstances, and an object thereof is to provide a steel sheet having excellent bendability and a small bending anisotropy, and a method for manufacturing the steel sheet.
[0014] Means for Solving the Problems
[0015] The present inventors have conducted detailed studies on the chemical composition, metal structure, and manufacturing conditions that affect the bending anisotropy of steel sheets. As a result, it has been found that by strictly controlling the anisotropy of the surface structure on the basis of forming a specified chemical composition and metal structure, the bending anisotropy can be reduced.
[0016] The present invention has been made in view of the above findings. The gist of the present invention is as follows.
[0017] (1) A steel sheet according to Embodiment 1 of the present invention, wherein the steel sheet has a chemical composition containing, by mass%:
[0018] C: 0.09 to 0.25%,
[0019] Si: 0.01 to 2.00%,
[0020] Mn: 1.5 to 3.5%,
[0021] P: 0.100% or less,
[0022] S: 0.0500% or less,
[0023] N: 0.0100% or less,
[0024] O: 0.0060% or less,
[0025] Al: 0 to 1.000%,
[0026] Cr: 0 to 2.000%,
[0027] Mo: 0 to 1.000%,
[0028] W: 0 to 1.000%,
[0029] Co: 0 to 0.500%,
[0030] B: 0 to 0.0100%,
[0031] Nb: 0 to 0.50%,
[0032] Ti: 0 to 0.5000%,
[0033] V: 0 to 0.500%,
[0034] Ta: 0 to 0.100%,
[0035] Sn: 0 to 0.050%
[0036] Sb: 0 to 0.050%,
[0037] As: 0 to 0.050%,
[0038] Ni: 0 to 1.000%,
[0039] Cu: 0 to 1.000%,
[0040] Ca: 0 to 0.050%,
[0041] Zr: 0 to 0.050%,
[0042] Mg: 0 to 0.050%, and
[0043] REM: 0 to 0.100%,
[0044] the balance consists of Fe and impurities;
[0045] in the metallographic structure at a position 1 / 4 of the plate thickness from the surface along the plate thickness direction, i.e., at the 1 / 4 depth position, by area ratio,
[0046] the total of ferrite and bainite is 0 to 40%,
[0047] martensite is 50 to 100%,
[0048] the total of pearlite and retained austenite is 0 to 10%;
[0049] in the metallographic structure in the region from the surface to 20 μm along the plate thickness direction, i.e., the surface soft part, by area ratio,
[0050] ferrite is 50% or more,
[0051] One or a total of two or more of martensite, bainite, pearlite, and retained austenite is 0 to 50%,
[0052] The ratio Hs / Hc of the Vickers hardness Hs of the surface soft part to the Vickers hardness Hc at the 1 / 4 depth position is 0.65 or less,
[0053] In the ferrite of the surface soft part, the Taylor factor M value M of the L section L and the Taylor factor M value M of the C section c The ratio M L / M c is 0.95 or more,
[0054] The aspect ratio of the island-shaped hard phase in the surface soft part is 3.0 or less and the major axis is 5.0 μm or less.
[0055] (2) Solution 2 of the present invention is in the steel plate of Solution 1,
[0056] The ultimate bending angle θ in the direction along the rolling direction L and the ultimate bending angle θ in the direction perpendicular to the rolling direction and the plate thickness direction C The ratio θ L / θ C can also exceed 0.80.
[0057] (3) Solution 3 of the present invention is in the steel plate of Solution 1 or Solution 2,
[0058] The tensile strength can also be 1180 MPa or more.
[0059] (4) Solution 4 of the present invention is in the steel plate of any one of Solutions 1 to 3,
[0060] When the tensile strength is 1180 to 1470 MPa, the ultimate bending angle θ C is 90° or more,
[0061] When the tensile strength exceeds 1470 MPa, the ultimate bending angle θ C can also be 80° or more.
[0062] (5) Solution 5 of the present invention is in the steel plate of any one of Solutions 1 to 4, and the plate thickness can also be 1.0 mm or more.
[0063] (6) Solution 6 of the present invention is in the steel plate of any one of Solutions 1 to 5,
[0064] The chemical composition may also contain, by mass%,
[0065] Al: 0.001 to 1.000%,
[0066] Cr: 0.001 to 2.000%,
[0067] Mo: 0.010 to 1.000%,
[0068] W: 0.001 to 1.000%,
[0069] Co: 0.010 to 0.500%,
[0070] B: 0.0001 to 0.0100%,
[0071] Nb: 0.01 to 0.50%,
[0072] Ti: 0.0001 to 0.5000%,
[0073] V: 0.001 to 0.500%,
[0074] Ta: 0.001 to 0.100%,
[0075] Sn: 0.001 to 0.050%,
[0076] Sb: 0.001 to 0.050%,
[0077] As: 0.001 to 0.050%,
[0078] Ni: 0.010 to 1.000%,
[0079] Cu: 0.001 to 1.000%,
[0080] Ca: 0.001 to 0.050%,
[0081] Zr: 0.001 to 0.050%,
[0082] Mg: 0.0001 to 0.050%, and
[0083] REM: 1 or more than 1 selected from 0.001 to 0.100%.
[0084] (7) The solution 7 of the present invention is that in the steel plate of any one of solutions 1 to 6,
[0085] it may also have a hot-dip galvanized layer on the said surface.
[0086] (8) The solution 8 of the present invention is that in the steel plate of any one of solutions 1 to 6,
[0087] it may also have an alloyed hot-dip galvanized layer on the said surface.
[0088] (9) The solution 9 of the present invention relates to a method for manufacturing a steel plate, which may also include:
[0089] A hot rolling process, in which a slab is heated and then hot rolling is performed in a first finishing mill stand starting at an average temperature of 850 °C or lower up to 10% of the thickness from the surface, thereby obtaining a hot rolled steel plate. The chemical composition of the slab contains, by mass%:
[0090] C: 0.09 - 0.25%,
[0091] Si: 0.01 - 2.00%,
[0092] Mn: 1.5 - 3.5%,
[0093] P: 0.100% or less,
[0094] S: 0.0500% or less,
[0095] N: 0.0100% or less,
[0096] O: 0.0060% or less,
[0097] Al: 0 - 1.000%,
[0098] Cr: 0 - 2.000%,
[0099] Mo: 0 - 1.000%,
[0100] W: 0 - 1.000%,
[0101] Co: 0 - 0.500%,
[0102] B: 0 - 0.0100%,
[0103] Nb: 0 - 0.50%,
[0104] Ti: 0 - 0.5000%,
[0105] V: 0 - 0.500%,
[0106] Ta: 0 - 0.100%,
[0107] Sn: 0 - 0.050%,
[0108] Sb: 0 - 0.050%,
[0109] As: 0 - 0.050%,
[0110] Ni: 0 - 1.000%,
[0111] Cu: 0 - 1.000%,
[0112] Ca: 0 to 0.050%,
[0113] Zr: 0 to 0.050%,
[0114] Mg: 0 to 0.050%, and
[0115] REM: 0 to 0.100%,
[0116] The balance consists of Fe and impurities;
[0117] A coiling process, which coils the hot-rolled steel sheet at a coiling temperature of 550 to 450°C after the hot-rolling process;
[0118] A holding process, which holds the hot-rolled steel sheet for 1 hour or more at a temperature higher than the coiling temperature and in the range of 650 to 500°C after the coiling process;
[0119] A cold-rolling process, which cold-rolls the hot-rolled steel sheet after the holding process under the conditions that the sheet thickness reduction rate is 20 to 80% and the average dynamic friction coefficient in the final 2 passes is 0.025 or more, thereby obtaining a cold-rolled steel sheet; and
[0120] An annealing process, which anneals the cold-rolled steel sheet after the cold-rolling process by holding it for 60 seconds or more in an atmosphere with a dew point of -30 to 20°C in the temperature range of 740 to 900°C.
[0121] Advantages of the Invention
[0122] According to the above solution of the present invention, a steel sheet with excellent bendability and less bend anisotropy and a method for manufacturing the steel sheet can be provided. Detailed Embodiments
[0123] The chemical composition, metallographic structure of the steel sheet of an embodiment of the present invention (hereinafter sometimes simply referred to as the steel sheet of the present embodiment), and rolling, annealing conditions, etc. in the manufacturing method capable of manufacturing the steel sheet are described in detail below.
[0124] The steel sheet of the present embodiment is applicable not only as a steel sheet without a coating on the surface, but also as a base material of a steel sheet with a coating formed on the surface. Here, the "base material" refers to the portion mainly composed of Fe in the central region of the plate thickness after removing the coating from the coated steel sheet. As such a coated steel sheet, for example, it includes a hot-dip galvanized steel sheet having a hot-dip galvanized layer on the surface, or an alloyed hot-dip galvanized steel sheet having an alloyed hot-dip galvanized layer on the surface. The main conditions shown below are also common features in base materials such as hot-dip galvanized steel sheets and alloyed hot-dip galvanized steel sheets.
[0125] <Chemical Composition>
[0126] First, the chemical composition of the steel plate of the present embodiment will be described. "%" indicating the content of each element in the chemical composition means mass% unless otherwise specified.
[0127] [C: 0.09 to 0.25%]
[0128] C (carbon) is an element necessary for the high strength of the steel plate. When the C content is less than 0.09%, sufficient tensile strength cannot be obtained. Therefore, the C content is set to 0.09% or more. The C content is preferably 0.11% or more.
[0129] On the other hand, if the C content exceeds 0.25%, the weldability decreases and the bendability deteriorates. Therefore, the C content is set to 0.25% or less. From the viewpoint of suppressing the deterioration of the press formability and weldability, the C content is preferably 0.20% or less.
[0130] [Si: 0.01 to 2.00%]
[0131] Si (silicon) is a solid solution strengthening element and is effective for the high strength of the steel plate. To obtain the above effects, the Si content is set to 0.01% or more. The Si content is preferably 0.30% or more.
[0132] On the other hand, if Si is excessively contained, embrittlement of the steel plate may sometimes occur, resulting in a decrease in manufacturability and workability. Therefore, the Si content is set to 2.00% or less. The Si content is preferably 1.50% or less.
[0133] [Mn: 1.5 to 3.5%]
[0134] Mn has the effect of improving the hardenability of steel and is an element effective for obtaining the desired metal structure. When the Mn content is less than 1.5%, it is difficult to obtain the desired metal structure. Therefore, the Mn content is set to 1.5% or more. The Mn content is preferably 2.0% or more.
[0135] On the other hand, when the Mn content exceeds 3.5%, the formation of ferrite on the surface layer in the hot-rolled steel plate and the annealed steel plate is suppressed, and the bendability and bend anisotropy cannot be improved. Therefore, the Mn content is set to 3.5% or less. The Mn content is preferably 3.0% or less.
[0136] [P: 0.100% or less]
[0137] P is an element that segregates at the grain boundaries, embrittles the steel, and deteriorates the bendability. Therefore, the less the P content, the more preferable, and it can also be 0%. Considering the removal time and cost of P, the P content is set to 0.100% or less. The P content is preferably 0.020% or less, and more preferably 0.010% or less.
[0138] [S: 0.0500% or less]
[0139] S is an element that forms sulfide inclusions and deteriorates bendability. Therefore, the lower the S content, the more preferable, and it can also be 0%. Considering the removal time and cost of S, the S content is set to 0.0500% or less. The S content is preferably 0.0100% or less, more preferably 0.0030% or less, and further preferably 0.0010% or less.
[0140] [N: 0.0100% or less]
[0141] N forms coarse nitrides in the steel sheet and is an element that deteriorates the bendability and hole expansion property of the steel sheet. When the N content exceeds 0.0100%, the above-mentioned deterioration becomes significant, so the N content is set to 0.0100% or less. The N content can also be 0.0090% or less, 0.0080% or less, or 0.0070% or less.
[0142] On the other hand, when the N content is set to less than 0.0001%, the manufacturing cost increases significantly. The N content can also be set to 0.0001% or more. The N content can also be set to 0.0005% or more.
[0143] [O: 0.0060% or less]
[0144] O is an element that forms coarse oxides in the steel and deteriorates bendability and hole expansion property. When the O content exceeds 0.0060%, the above-mentioned deterioration becomes significant. Therefore, the O content is set to 0.0060% or less. The O content can also be 0.0050% or less, 0.0040% or less, or 0.0030% or less.
[0145] The O content is preferably less. However, setting the O content to less than 0.0001% will cause excessive cost increase and is not economically preferable. Therefore, the O content can also be set to 0.0001% or more. The O content can also be set to 0.0010% or more.
[0146] The steel sheet of this embodiment may also contain the above elements, and the remaining part includes Fe and impurities. Here, impurities are elements mixed due to various factors such as raw materials like ore and scrap, and manufacturing processes during industrial steel production, and are elements allowed to exist within the range that does not hinder the characteristics of the steel sheet of this embodiment. Additionally, it also includes elements that do not mean intentionally added components to the steel sheet.
[0147] For the purpose of improving various properties, the steel plate of the present embodiment may further contain one or more elements (optional elements) selected from Al, Cr, Mo, W, Co, B, Nb, Ti, V, Ta, Sn, Sb, As, Ni, Cu, Ca, Zr, Mg, and REM as shown below. Since the optional elements may not be contained, the lower limit is 0%. In addition, even if the following elements are contained as impurities, the effects of the steel plate of the present embodiment will not be hindered.
[0148] [Al: 0 to 1.000%]
[0149] Al is an element having a deoxidizing effect on steel. Therefore, Al may also be contained in the steel. In order to obtain the above effects, the Al content is preferably set to 0.001% or more. The Al content is preferably 0.005% or more.
[0150] On the other hand, even if Al is contained in excess, the effects are saturated, which not only leads to an increase in cost but also an increase in the phase transformation temperature of the steel and an increase in the load during hot rolling. Therefore, the Al content is set to 1.000% or less. The Al content is preferably 0.900% or less.
[0151] [Cr: 0 to 2.000%]
[0152] Cr is an element effective in improving hardenability and strengthening the steel plate. Therefore, Cr may also be contained in the steel. In order to strengthen the steel plate by Cr to improve hardenability, the Cr content is preferably 0.001% or more. On the other hand, if the Cr content exceeds 2.000%, Cr may segregate in the center of the steel plate to form coarse Cr carbides, reducing the cold formability. Therefore, the Cr content is set to 2.000% or less.
[0153] [Mo: 0 to 1.000%]
[0154] Mo is an element effective in strengthening the steel plate. Therefore, Mo may also be contained in the steel. In order to strengthen the steel plate by Mo, the Mo content is preferably 0.010% or more.
[0155] On the other hand, if the Mo content exceeds 1.000%, the cost sometimes increases, and coarse Mo carbides are formed, reducing the cold workability of the steel plate. Therefore, the Mo content is set to 1.000% or less.
[0156] [W: 0 to 1.000%]
[0157] W is a carbide-forming element and is an element effective in strengthening the steel plate. Therefore, W may also be contained in the steel. In order to obtain the above effects, the W content is preferably 0.001% or more. The W content is more preferably 0.005% or more. The W content is further preferably 0.010% or more.
[0158] On the other hand, even if the content of W is excessive, the effect is saturated, resulting in an increase in cost. Therefore, when W is contained, the content of W is set to 1.000% or less. The content of W is more preferably 0.600% or less. The content of W is more preferably 0.100% or less.
[0159] [Co: 0 to 0.500%]
[0160] Co is an element effective in improving the strength of the steel plate. Therefore, Co can also be contained in the steel. In order to obtain the above effects, the content of Co is preferably 0.010% or more, and more preferably 0.050% or more.
[0161] On the other hand, if the content of Co is excessive, the ductility of the steel plate decreases, which may lead to a decrease in hole expansion and bendability. Therefore, the content of Co is set to 0.500% or less. The content of Co is more preferably 0.400% or less.
[0162] [B: 0 to 0.0100%]
[0163] B is an element that suppresses the formation of ferrite and pearlite and promotes the formation of low-temperature transformation structures such as bainite or martensite during the cooling process from austenite. In addition, B is an element beneficial to the high strength of the steel plate. Therefore, B can also be contained in the steel. In order to obtain the above effects produced by B, the content of B is preferably 0.0001% or more.
[0164] On the other hand, when the content of B exceeds 0.0100%, the formation of coarse B oxides and borides in the steel is caused, which becomes the generation starting point of pores during press forming, and sometimes deteriorates the workability of the steel plate. Therefore, the content of B is set to 0.0100% or less.
[0165] [Nb: 0 to 0.50%]
[0166] Nb is an element effective in controlling the morphology of carbides. By containing it, the structure is refined, and it is also an element effective in improving the toughness of the steel plate. Therefore, Nb can also be contained in the steel. In order to obtain the effects produced by Nb, the content of Nb is preferably set to 0.01% or more.
[0167] On the other hand, if the content of Nb exceeds 0.50%, a large amount of coarse Nb carbides precipitate, which becomes the generation starting point of pores during press forming, and sometimes deteriorates the workability of the steel plate. Therefore, the content of Nb is set to 0.50% or less.
[0168] [Ti: 0 to 0.5000%]
[0169] Ti is an element important for controlling the morphology of carbides and is an element that promotes an increase in the strength of ferrite by being contained in a large amount. Therefore, Ti can also be contained in the steel. In order to obtain this effect, the Ti content is preferably set to 0.0001% or more.
[0170] On the other hand, if the Ti content exceeds 0.5000%, coarse Ti oxides or Ti carbonitrides are present in the steel, sometimes reducing the workability of the steel plate. Therefore, the Ti content is set to 0.5000% or less.
[0171] [V: 0 to 0.500%]
[0172] V is an element effective for controlling the morphology of carbides. By containing it, the structure is refined, and thus it is also an element effective for improving the toughness of the steel plate. Therefore, V can also be contained in the steel. In order to obtain this effect caused by V, the V content is preferably 0.001% or more.
[0173] On the other hand, if the V content exceeds 0.500%, a large amount of fine V carbides precipitate, the strength of the steel plate increases, and the ductility significantly deteriorates, sometimes reducing the workability. Therefore, the V content is set to 0.500% or less.
[0174] [Ta: 0 to 0.100%]
[0175] Ta is an element effective for controlling the morphology of carbides and for increasing the strength of the steel plate. Therefore, Ta can also be contained in the steel. In order to obtain the above effects, the Ta content is preferably 0.001% or more.
[0176] On the other hand, if the Ta content is excessive, a large amount of fine Ta carbides precipitate, resulting in a decrease in the ductility of the steel plate, and it is possible to reduce the hole expansion property and bendability of the steel plate. Therefore, the Ta content is set to 0.100% or less. The Ta content is more preferably 0.020% or less. The Ta content is further preferably 0.011% or less.
[0177] [Sn: 0 to 0.050%]
[0178] Sn is an element that can be contained in the steel plate when using scrap as a raw material for the steel plate. In addition, Sn may cause a decrease in the hole expansion property and bendability of the steel plate due to the embrittlement of ferrite. Therefore, the less the Sn content, the more preferable. In order to suppress the decrease in the hole expansion property and bendability of the steel plate, the Sn content is set to 0.050% or less. The Sn content is preferably 0.040% or less. The Sn content can also be 0%. However, reducing the Sn content to less than 0.001% will cause an excessive increase in the refining cost. Therefore, the Sn content can also be set to 0.001% or more.
[0179] [Sb: 0 to 0.050%]
[0180] Like Sn, Sb is an element that can be contained in steel sheets when using scrap as a raw material for steel sheets. Sb strongly segregates at grain boundaries, which may lead to embrittlement of grain boundaries and a decrease in ductility, and further lead to a decrease in hole expansion and bendability. Therefore, the lower the Sb content, the more preferable. In order to suppress the reduction in properties caused by the above effects, the Sb content is set to 0.050% or less. The Sb content is preferably 0.040% or less. The Sb content can also be 0%. However, reducing the Sb content to less than 0.001% will cause an excessive increase in refining costs. Therefore, the Sb content can also be set to 0.001% or more.
[0181] [As: 0 to 0.050%]
[0182] Like Sn and Sb, As is an element that can be contained in steel sheets when using scrap as a raw material for steel sheets. As strongly segregates at grain boundaries, which may lead to a decrease in hole expansion and bendability. Therefore, the lower the As content, the more preferable. In order to suppress the reduction in hole expansion and bendability, the As content is set to 0.050% or less. The As content is preferably 0.040% or less. The As content can also be 0%. However, reducing the As content to less than 0.001% will cause an excessive increase in refining costs. Therefore, the As content can also be set to 0.001% or more.
[0183] [Ni: 0 to 1.000%]
[0184] Ni is an element effective in improving the strength of steel sheets. Therefore, Ni can also be contained in the steel. In order to obtain the above effects, the Ni content is preferably 0.001% or more. The Ni content is more preferably 0.010% or more. On the other hand, if the Ni content is too high, the ductility of the steel sheet decreases, which may lead to a decrease in hole expansion and bendability. Therefore, the Ni content is set to 1.000% or less. The Ni content is preferably 0.800% or less.
[0185] [Cu: 0 to 1.000%]
[0186] Cu is an element that helps to improve the strength of steel sheets. Therefore, Cu can also be contained in the steel. In order to obtain the above effects, the Cu content is preferably 0.001% or more. However, if the Cu content is too high, it will cause red-hot brittleness and may reduce the productivity in hot rolling. Moreover, if the Cu content is too high, it may cause a decrease in hole expansion and bendability due to the formation of coarse inclusions. Therefore, the Cu content is set to 1.000% or less. The Cu content is preferably 0.500% or less.
[0187] [Ca: 0 to 0.050%]
[0188] Ca is an element that can control the morphology of sulfides in trace amounts. Therefore, Ca can also be contained in steel. To achieve the above effects, the Ca content is preferably 0.001% or more. However, if the Ca content is excessive, sometimes coarse Ca oxides are formed, and these Ca oxides become the starting points for crack generation during cold forming. As a result, the hole expansion property and bendability may deteriorate. Therefore, the Ca content is set to 0.050% or less. The Ca content is preferably 0.030% or less.
[0189] [Zr: 0 to 0.050%]
[0190] Zr is an element that can control the morphology of sulfides in trace amounts. Therefore, Zr can also be contained in steel. To achieve the above effects, the Zr content is preferably 0.001% or more. However, if the Zr content is excessive, coarse Zr oxides are formed, and the hole expansion property and bendability may decrease. Therefore, the Zr content is set to 0.050% or less. The Zr content is preferably 0.040% or less.
[0191] [Mg: 0 to 0.050%]
[0192] Mg is an element that controls the morphology of sulfides and oxides and helps improve the bendability of the steel plate. Therefore, Mg can also be contained in steel. To achieve these effects, the Mg content is preferably 0.0001% or more. However, if the Mg content is excessive, the hole expansion property and bendability may decrease due to the formation of coarse inclusions. Therefore, the Mg content is set to 0.050% or less. The Mg content is preferably 0.040% or less.
[0193] [REM: 0 to 0.100%]
[0194] REM is Rare Earth Metal. REM is an element that effectively acts on the morphology control of sulfides even in trace amounts. Therefore, REM can also be contained in steel. To achieve the above effects, the REM content is preferably 0.001% or more. However, if the REM content is excessive, coarse REM oxides are formed, and the workability, fracture resistance characteristics, hole expansion property, and bendability may decrease. Therefore, the REM content is set to 0.100% or less, preferably 0.059% or less.
[0195] Here, REM refers to the general term for two elements, scandium (Sc) and yttrium (Y), and 15 elements from lanthanum (La) to lutetium (Lu) (lanthanide elements). In addition, "REM" in the present embodiment is composed of one or more selected from these rare earth elements, and the "REM content" refers to the total amount of rare earth elements.
[0196] The chemical composition of the steel plate of the present embodiment can be determined by the following method.
[0197] The chemical composition of the above steel plate can be determined according to general chemical compositions. For example, ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) can be used for determination. Additionally, C and S can be determined by combustion-infrared absorption method, N can be determined by inert gas fusion-thermal conductivity method, and O can be determined by inert gas fusion-non-dispersive infrared absorption method. When the steel plate has a coating on its surface, the coating can be removed by mechanical grinding and then the chemical composition can be analyzed. Regarding the boundary between the coating and the steel plate, the C concentration is measured in the thickness direction of the steel plate using GDS (Glow Discharge Emission Spectrometry), and the position where the C concentration becomes the minimum value within the range from the detection start point of C to a depth of 200 μm in the thickness direction is regarded as the boundary between the coating and the steel plate. In the following description, regarding the description of "(the surface of the) steel plate", in the steel plate with a coating on its surface, the above boundary is regarded as "(the surface of the) steel plate".
[0198] <Metallographic structure at 1 / 4 depth position>
[0199] Next, the metallographic structure at the 1 / 4 depth position (the position along the thickness direction and at 1 / 4 of the plate thickness from the surface) of the steel plate of the present embodiment will be described.
[0200] In the description of the metallographic structure of the steel plate of the present embodiment, the volume fraction of the structure is expressed as an area ratio. Therefore, unless otherwise specified, "%" means "area %". In the present embodiment, the surface serving as the reference for the 1 / 4 depth position, in the case of a coated steel plate, refers to the surface of the base steel plate excluding the coating.
[0201] In the structure at the 1 / 4 depth position (along the thickness direction, i.e., the direction perpendicular to the surface of the steel plate, and at 1 / 4 of the plate thickness from the surface of the steel plate) of the steel plate of the present embodiment (including steel plate, hot-dip galvanized steel plate, and alloyed hot-dip galvanized steel plate), the total area ratio of ferrite and bainite is 0 - 40%, the area ratio of martensite is 50 - 100%, and the total area ratio of pearlite and retained austenite is 0 - 10%.
[0202] (The total area ratio of ferrite and bainite is 0 - 40%)
[0203] Ferrite is a soft phase formed by slow cooling after holding in a two-phase region annealing or annealing process. When ferrite coexists with a hard phase such as martensite, the ductility of the steel plate is improved. However, in order to achieve a specified high strength, the area ratio of ferrite needs to be restricted.
[0204] In addition, bainite is usually a phase formed by holding for a certain period of time at 350 to 450°C during the cooling process after holding at the annealing temperature. Bainite is softer than martensite and thus has the effect of improving ductility. However, in order to achieve a specified high strength, it is necessary to limit its area ratio in the same way as the above-mentioned ferrite.
[0205] Therefore, the total area ratio of ferrite and bainite is set to 40% or less. Preferably, it is 30% or less. It is also possible not to contain ferrite and bainite, and thus the lower limit is 0%. In addition, the area ratio of each of ferrite and bainite is not limited.
[0206] (The area ratio of martensite is 50 to 100%)
[0207] Martensite is a hard structure and thus contributes to the improvement of tensile strength. In order to obtain the desired strength, the area ratio of martensite is set to 50% or more. The area ratio of martensite is preferably 70% or more, more preferably 85% or more. Thereby, it is easy to ensure a high tensile strength (for example, a tensile strength of 1180 MPa or more). From the viewpoint of strength, the area ratio of martensite can also be 100%.
[0208] In addition, in the present embodiment, "martensite" refers to both primary martensite and tempered martensite. That is, in the present embodiment, the "area ratio of martensite" refers to the "total of the area ratios of primary martensite and tempered martensite". "Primary martensite" refers to martensite that does not contain iron carbide. In addition, "tempered martensite" is martensite that contains iron carbide.
[0209] From the viewpoints of toughness, hole expansion property, and ductility, the area ratio of tempered martensite is preferably high, but the area ratio of each of martensite and tempered martensite is not limited. The degree of tempering can be adjusted within a normal range according to the required levels of strength, toughness, hole expansion property, and ductility.
[0210] (The total area ratio of pearlite and retained austenite is 0 to 10%)
[0211] Pearlite is a hard structure in which soft ferrite and hard cementite are arranged in layers, and it is a structure that contributes to the improvement of the tensile strength of the steel sheet. In addition, retained austenite is a structure that contributes to the improvement of the elongation rate through transformation-induced plasticity (TRIP). It is also possible not to contain pearlite and retained austenite, and thus the lower limit of the area ratio of each is 0%.
[0212] Pearlite is a structure with cementite in the structure, consuming C (carbon) in the steel that helps improve strength. Therefore, if the area ratio of pearlite is excessive, the strength of the steel plate decreases. In addition, if the area ratio of retained austenite is excessive, the grain size of the retained austenite increases. Such retained austenite with a large grain size becomes coarse and hard martensite after deformation. In this case, the starting point of cracking is likely to occur, deteriorating the bendability. Therefore, the total area ratio of pearlite and retained austenite is set to 0 to 10%. For example, the area ratio of pearlite is set to 5.0% or less. The area ratio of pearlite is preferably 3.0% or less, more preferably 1.0% or less. The area ratio of retained austenite is, for example, set to 10.0% or less. It is preferably 5.0% or less.
[0213] Next, the method for identifying each metal structure and calculating the area ratio at the 1 / 4 depth position will be described.
[0214] Regarding the identification of each metal structure and the calculation of the area ratio, for a specified observation area, the area that should initially be retained austenite is determined, and then, for the same observation area, ferrite, bainite, martensite, or pearlite is identified.
[0215] The area and area ratio of retained austenite are measured by the following method. That is, the observation surface is finish-machined by colloidal silica polishing or electrolytic polishing, and using EBSD attached to a scanning electron microscope, at a position 1 / 4 of the plate thickness from the surface of the steel plate, in a 100 μm × 100 μm square area, diffraction electrons are measured at intervals of 0.2 μm (lattice configuration) in the plate thickness direction and the rolling direction respectively, and the obtained pseudo-Kikuchi pattern is analyzed to identify the crystal orientation and crystal system. In addition, the specimen preparation conditions, etc. are set within the range of the conditions recommended in the Japan Society for Materials Science standard "Standard for Determination of Crystal Orientation Difference for Material Evaluation Based on Electron Backscatter Diffraction (EBSD) Method". The area detected as the FCC phase from the measurement data is regarded as retained austenite, and its area and area ratio are measured.
[0216] In addition, the method for discriminating the rolling direction is as described later.
[0217] The areas and area ratios of ferrite, bainite, martensite, and pearlite can be measured by the following method. That is, the same square area as that for observing the retained austenite in the above implementation is etched with a nitric acid ethanol etching solution, and photographed with a field emission scanning electron microscope (FE-SEM: Field Emission Scanning Electron Microscope) (magnification: 5000 times). The ratio of each tissue obtained by the point counting method with a 2-μm interval (lattice configuration) from the obtained tissue photograph is used as the area ratio.
[0218] Each tissue is determined by the following method. Ferrite is in a granular or acicular form and does not contain iron-based carbides inside. Bainite is in a lath form (lath structure), and there are iron-based carbides with a major axis of 20 nm or more inside the lath structure, and it is the area where the carbides extend in the same direction. Martensite is in a lath form (lath structure), and it is the area that does not contain iron-based carbides with a major axis of 20 nm or more inside the lath structure. Tempered martensite is in a lath form (lath structure), and it is the area where there are iron-based carbides with a major axis of 20 nm or more inside the lath structure and the carbides extend in multiple different directions. In addition, the area where ferrite and cementite are in a flaky form is regarded as pearlite.
[0219] In addition, in the identification of ferrite, bainite, martensite, and pearlite, for the areas determined as retained austenite in the identification of retained austenite before them, the above-mentioned visual identification is not performed. However, the area ratio is calculated as the ratio to the total area of the observation range including the retained austenite area.
[0220] The judgment of these metal microstructures is usually carried out by those skilled in the art as ordinary operations, and those skilled in the art can easily determine.
[0221] When the total area ratio of each tissue obtained by the above evaluation method is not 100%, the value obtained by multiplying the area ratio of each tissue by 100 / (the total area ratio of each tissue) is used as the area ratio of each tissue.
[0222] <Metal microstructure of the surface soft part>
[0223] Along the thickness direction of the steel plate of this embodiment, the area from the surface of the steel plate to 20 μm is regarded as the surface soft part. In other words, the area starting from the surface of the steel plate and ending at a depth of 20 μm from the surface is regarded as the surface soft part.
[0224] In the metal microstructure of the surface soft part of the steel plate of this embodiment, in terms of area ratio, ferrite is 50% or more, and the total of one or more of martensite, bainite, pearlite, and retained austenite is 0% to 50%.
[0225] [The area ratio of ferrite is 50% or more]
[0226] When ferrite coexists with a hard phase such as martensite, the ductility of the steel plate is improved. In order to improve the bendability of the steel plate, the area ratio of ferrite in the surface soft part is set to 50% or more. More preferably, the area ratio of ferrite in the surface soft part is 60% or more. The upper limit of the area ratio of ferrite can also be 100%.
[0227] [The total area ratio of one or more of martensite, bainite, pearlite, and retained austenite is 0 to 50%]
[0228] If the total area ratio of one or more of martensite, bainite, pearlite, and retained austenite in the surface soft part exceeds 50%, the bendability of the steel plate of the present embodiment may deteriorate. Therefore, the total area ratio of one or more of martensite, bainite, pearlite, and retained austenite in the surface soft part is set to 50% or less. It is also possible not to contain martensite, bainite, pearlite, and retained austenite in the surface soft part, and thus the lower limit of each is 0%.
[0229] Next, a method for identifying each metal structure in the surface soft part and calculating the area ratio will be described.
[0230] For the identification of each metal structure and the calculation of the area and area ratio, except for the measurement position, the method for calculating the area ratio of each metal structure at the 1 / 4 depth position can be used. The measurement area is set to a square area from the surface of the steel plate to a depth of 20 μm (a square area of 20 μm × 20 μm in the rolling direction with one side being the surface of the steel plate).
[0231] [The ratio of the Vickers hardness of the surface soft part to the Vickers hardness at the 1 / 4 depth position]
[0232] The ratio Hs / Hc of the Vickers hardness Hs of the surface soft part of the steel plate of the present embodiment to the Vickers hardness Hc at the 1 / 4 depth position is 0.65 or less. By making Hs / Hc 0.65 or less, the bendability of the steel plate can be improved.
[0233] The Vickers hardness of the soft surface layer of the steel plate and the Vickers hardness at the 1 / 4 depth position can be measured according to the following steps. First, the plate thickness cross-section parallel to the plane formed by the rolling direction and the plate thickness direction of the steel plate is machined into a mirror surface by mechanical grinding. In this ground surface, from the surface of the steel plate towards the inside of the plate thickness, for each depth position of 5 μm distance (depth), 10 μm distance (depth), 15 μm distance (depth), and 20 μm distance (depth), at 12 positions on a straight line parallel to the rolling direction, according to JIS Z 2244-1:2020, the Vickers hardness (HV) is measured with an indentation load of 20 gf. The 12 measurement points at each plate thickness position are measured at intervals of more than 3 indentation sizes. The average of the Vickers hardness of 10 points after removing the lowest value and the highest value from the Vickers hardness of the 12 points measured at each depth position is taken as the Vickers hardness at that depth position. The average of the Vickers hardness at each depth position is taken as the Vickers hardness (Hs) of the soft surface layer of the steel plate.
[0234] Similarly, in the ground surface, at 12 positions on a straight line parallel to the rolling direction and at a distance (depth) of 1 / 4 of the plate thickness from the surface of the steel plate towards the inside of the plate thickness, the Vickers hardness (HV) is measured with an indentation load of 20 gf. The average of the Vickers hardness of 10 points after removing the lowest value and the highest value from the Vickers hardness of the 12 measured points is taken as the Vickers hardness (Hc) at the 1 / 4 depth position of the steel plate.
[0235] In addition, the interval between each measurement point is preferably set to a distance of more than 4 times the indentation. The distance of more than 4 times the indentation described here refers to the distance obtained by multiplying the length of the diagonal of the indentation generated by the diamond indenter by a value of more than 4 times when measuring the Vickers hardness.
[0236] <Ratio of Taylor factor M values of L-section to C-section of ferrite in soft surface layer>
[0237] In the ferrite of the soft surface layer, the ratio of the Taylor factor M value of the L-section to the C-section is 0.95 or more. That is, the Taylor factor M value M of the L-section L and the Taylor factor M value M of the C-section c The ratio M L / M c is 0.95 or more. M L / M c More preferably, it is 0.97 or more. M L / M c It can also be 1.20 or less. The ratio M L / M c More preferably, it is 1.10 or less.
[0238] The M value refers to the ratio of the yield stress to the critical resolved shear stress during uniaxial tension of a polycrystal, and is called the Taylor factor. The M value of the surface soft part defined in this way can also be said to be the greatest feature of the steel plate of this embodiment. By controlling the crystal orientation of the surface soft part of the steel plate of this embodiment so that the ratio of the L section to the C section of the Taylor factor M value is 0.95 or more, problems related to the in-plane anisotropy of the bending deformation of the steel plate are eliminated. The reason is not clear yet, but the following can be considered. It is known that the generation of cracks in bending deformation is related to the formation of shear bands, and the crystal texture has a strong influence on the formation of shear bands. The M value is the sum of shear slips, and a large M value means that unevenness due to slip is likely to form on the outermost surface. It is considered that such unevenness on the outermost surface causes the generation of cracks in bending deformation. Therefore, by making the ratio of the M value of the L section to the M value of the C section close to 1, the in-plane anisotropy of the bendability of the steel plate can be effectively alleviated.
[0239] The Taylor factor M value can be obtained by the following steps. Using the electron backscatter diffraction (EBSD) device attached to a scanning electron microscope, in a region of 20 μm depth in the plate thickness direction from the surface, that is, in the direction perpendicular to the steel plate surface, and 50 μm length in the rolling direction (L section), and in a region of 20 μm depth in the plate thickness direction and 50 μm length in the direction perpendicular to the rolling direction (C section), measurements are performed at intervals (pitches) of 0.2 μm for the plate thickness direction and the rolling direction or the direction perpendicular to the rolling, respectively. Calculate the value of the grain average misorientation (GAM) based on the measurement data. Then, the region where the value of the grain average misorientation is less than 0.5° is regarded as ferrite, and only the data of this part is extracted. For the crystal orientation data of only the extracted ferrite, calculations are performed using the "Taylor factor" calculation model with OIM software. As the slip system considered at this time, only {110}<111> is considered. In addition, as the strain tensor, the tensor represented by the following formula (1) is used. The average value of the M values of all ferrite grains in the measurement field of view is taken as the M value of the ferrite in the surface soft part of its section. It is obtained in the L section and the C section, and the ratio is calculated.
[0240] [Mathematical formula 1]
[0241]
[0242] <Aspect ratio and major axis of the island-shaped hard phase in the surface soft part>
[0243] In order to reduce the anisotropy of bendability, the morphology of the island-shaped hard phase in the surface soft part is also an important factor. The aspect ratio of the island-shaped hard phase in the surface soft part is 3.0 or less, and the major axis of the island-shaped hard phase is 5.0 μm or less. The aspect ratio of the island-shaped hard phase can also be 1.0 or more. By making the aspect ratio of the island-shaped hard phase in the surface soft part 3.0 or less and making the major axis of the island-shaped hard phase 5.0 μm or less, the anisotropy of bendability can be reduced. The major axis of the island-shaped hard phase can also be 1.0 μm or more. The island-shaped hard phase refers to a phase composed of one or more of martensite and retained austenite. This island-shaped hard phase is an area surrounded by other phases (ferrite or bainite or pearlite).
[0244] The aspect ratio of the island-shaped hard phase can be calculated as follows: For a region with a depth of 20 μm in the plate thickness direction and a length of 50 μm in the rolling direction starting from the surface, the regions of ferrite, bainite, martensite, pearlite, and retained austenite are determined by the aforementioned means, and the major axis and minor axis of the island-shaped hard phase (a phase composed of one or more of martensite and retained austenite) present in the observation field of view are measured and calculated. Here, the major axis and minor axis are determined as follows.
[0245] First, for an island-shaped hard phase, consider taking the rolling direction as the x-axis and clamping the island-shaped hard phase from both sides with two parallel lines perpendicular to the x-axis. The distance between the two parallel lines at this time is taken as the size of the island-shaped hard phase in the rolling direction. Furthermore, take the direction inclined 1° from the rolling direction as the x-axis and determine the size of the island-shaped hard phase in the 1° direction. Similarly, imagine tilting the x-axis by 1° relative to the rolling direction until 179° to obtain the size of the island-shaped hard phase. In this way, regarding the size of the island-shaped hard phase, 180 data for each 1° from the 0° direction to the 179° direction are obtained. The maximum value among the 180 data is taken as the major axis of the island-shaped hard phase. In addition, the minimum value is taken as the minor axis of the island-shaped hard phase. The value obtained by dividing the major axis thus obtained by the minor axis is taken as the aspect ratio of the island-shaped hard phase.
[0246] In the present embodiment, the major axis and aspect ratio are determined for all the island-shaped hard phases present in the above-mentioned observation field of view. Then, the average value of the major axes of all the island-shaped hard phases in the observation field of view is taken as the major axis of the island-shaped hard phase in the surface soft part of the steel plate. In addition, the average value of the aspect ratios of all the island-shaped hard phases in the observation field of view is defined as the value of the aspect ratio of the island-shaped hard phase in the surface soft part.
[0247] In addition, in the present embodiment, the rolling direction is discriminated by the following method.
[0248] First, test pieces are collected in a manner that allows the cross-section of the plate thickness of the steel plate to be observed. After finishing the cross-section of the collected test pieces by mirror polishing, they are observed using an optical microscope. The observation range is set to a range of 500 μm in width × the total plate thickness, and regions with a darker brightness are determined as inclusions. Next, based on the cross-section of the plate thickness initially observed by the above method, it is rotated at intervals of 5° within the range of 0° to 180° with the plate thickness direction as the axis, and cross-section observations are performed on the planes parallel to the planes obtained by such rotation. The average value of the lengths of the major axes of the inclusions in each cross-section obtained for each cross-section is calculated. The direction parallel to the major axis direction of the inclusions in the cross-section with the maximum average value of the lengths of the major axes of the inclusions is determined as the rolling direction.
[0249] In the case where inclusions with a large aspect ratio are not observed, the Z-plane of the plate (the plane perpendicular to both the length direction and the width direction of the plate) is ground to a depth of 1 / 4t of the plate thickness, and after finishing by mirror polishing, an Mn concentration distribution map of a 500 μm × 500 μm region is obtained by EPMA. In the case where the solidification segregation of Mn is measured to be striated, the length direction of the stripe pattern is determined as the rolling direction.
[0250] In addition, in the case where the rolling direction of the steel plate is previously determined, the rolling direction of the steel plate may not be determined by the above determination method. Also, even when the steel plate is processed into a component, the above method can be used to determine the rolling direction of the weakly processed part of the component (for example, a relatively unprocessed flat part).
[0251] Generally speaking, a technique for improving the bendability of a steel plate by softening the surface layer of the steel plate is known. However, the softening of the surface layer of the steel plate in the present embodiment has a more preferable effect in addition. Specifically, the softening of the surface layer of the steel plate also effectively functions for "suppressing the in-plane anisotropy of the bending characteristics", which is also the maximum effect of the present invention. The reason is not clear, but the following can be considered. The steel plate of the present embodiment is a steel plate that utilizes a phase using a phase change as a metal structure, and the morphology of grains and precipitates (Fe carbides) is likely to have anisotropy. In a steel plate with such a structure, when softening is achieved, for example, additional heat treatment, decarburization, etc. are applied. Then, it can be considered that the anisotropy of the morphology of grains and precipitates also acts in the direction of relaxation, and it can be considered that the morphology is particularly improved on the surface layer of the steel plate, thus particularly effectively suppressing the in-plane anisotropy of the bending characteristics.
[0252] [Mechanical properties]
[0253] [Tensile strength is 1180 MPa or more]
[0254] [When the direction along the rolling direction is used as the bending ridge line, the limit bending angle θL 、When the bending ridge line is in the direction perpendicular to the rolling direction and the plate thickness direction, the limit bending angle θ C Ratio θ L / θ C Exceeds 0.80]
[0255] [In the case where the tensile strength is 1180 - 1470 MPa, the limit bending angle θ C Is 90° or more, and in the case where the tensile strength exceeds 1470 MPa, the limit bending angle θ C Is 80° or more]
[0256] In the steel plate of the present embodiment, as the strength contributing to the weight reduction of the automobile body, the tensile strength (TS) is preferably set to 1180 MPa or more. From the viewpoint of impact absorbability, the strength of the steel plate is preferably 1400 MPa or more, and more preferably 1470 MPa or more.
[0257] In addition, from the viewpoint of bending anisotropy, the limit bending angle θ L In the direction along the rolling direction and the limit bending angle θ C Ratio θ L / θ C Is preferably set to exceed 0.80. θ L / θ C More preferably, it is 0.85 or more, and even more preferably 0.90 or more.
[0258] In addition, in the case where the tensile strength is 1180 - 1470 MPa, the limit bending angle θ C Is preferably set to 90° or more. More preferably, it is 95° or more, and even more preferably 100° or more. In the case where the tensile strength exceeds 1470 MPa, the limit bending angle θ C Is preferably set to 80° or more. More preferably, it is 85° or more, and even more preferably 90° or more.
[0259] The tensile strength (TS) can be obtained by collecting JIS No. 5 tensile test pieces from the steel plate in the direction perpendicular to the rolling direction and the plate thickness direction and performing a tensile test in accordance with JIS Z 2241:2022.
[0260] In addition, the limit bending angle can be obtained by a bending test in accordance with VDA (German Automotive Industry Association Standard) 238 - 100. The limit bending angle when the bending ridge line is in the direction parallel to the direction along the rolling direction is set as the limit bending angle θ LThe limit bending angle when the direction parallel to the direction perpendicular to the rolling direction and the plate thickness direction is defined as the bending ridge line is set as the limit bending angle θ of the direction perpendicular to the rolling direction and the plate thickness direction. C 。
[0261] In the steel plate of the present embodiment, particularly by appropriately controlling the bending anisotropy, the impact absorbability can be improved. The reason is not yet clear, but the following can be considered. It is assumed that the deformation of the strength member associated with the steel plate of the present embodiment during a collision mainly becomes bending deformation. The bending deformation at this time is very complex, and due to the anisotropy of the shape of the member and the anisotropy of the deformation stress during the collision, it should be considered that the bending deformation of the member will not occur uniformly. The non-uniformity of this deformation can be considered by a model in which particularly small bending deformations bend in various directions in each local area of the steel plate surface. In this way, the bending deformation is concentrated in the part (bending direction) where the resistance to the bending deformation is small, fracture of this area occurs, and the undeformed area expands, thereby reducing the impact absorption amount of the entire member. In the steel plate of the present embodiment, by appropriately controlling the in-plane anisotropy of the limit bending angle, local deformation of the member is avoided, and the strain caused by the deformation during the collision is propagated to the entire member. Thereby, the impact absorbability of the member can be improved.
[0262] <Thickness>
[0263] The thickness of the steel plate of the present embodiment is not limited, but considering its application to impact absorbing members, it is preferably 0.5 mm or more. A more preferable thickness is 1.0 mm or more. The thickness of the steel plate can also be set to 3.0 mm or less, for example. The thickness of the steel plate can also be set to 2.0 mm or less.
[0264] The thickness is obtained by measuring the thickness at at least three locations of the steel plate and calculating the average value thereof.
[0265] In the steel plate of the present embodiment, a hot-dip galvanized layer may be provided on the surface. By providing a coating on the surface, the corrosion resistance is improved. For automotive steel plates, if there is a concern about perforation due to corrosion, sometimes even with high strength, it cannot be thinned to less than a certain plate thickness. One of the purposes of high strength of steel plates is weight reduction based on thinning. Therefore, even if a steel plate is developed, if its corrosion resistance is low, the application parts are limited. As a method for solving these problems, plating such as hot-dip galvanizing with high corrosion resistance can be considered for the steel plate. Since the steel plate of the present embodiment controls the steel plate composition as described above, hot-dip galvanizing can be performed. The hot-dip galvanized layer may also be an alloyed hot-dip galvanized layer.
[0266] Whether the steel sheet has a hot-dip galvanized layer or an alloyed hot-dip galvanized coating system is determined by the following method. Using an energy-dispersive X-ray spectrometer (EDS), in the cross-section of a specimen containing the coating and the parent phase, line analysis is performed in a direction perpendicular to the interface between the coating and the parent phase. The concentration distribution of each element from the coating side towards the parent phase direction is obtained. When a region with a high Fe concentration of 5% or more exists at an interface of 1 μm or more relative to the average composition from the surface of the coating to a depth of 2 μm in the plate thickness direction, it is determined to have an alloyed hot-dip galvanized coating system, otherwise, it is determined to have a hot-dip galvanized layer. In addition, the quantification of the concentration is carried out by the ZAF method.
[0267] The steel sheet of this embodiment can also be processed into a component shape. That is to say, the steel sheet of this embodiment can also be a component including this steel sheet. Even when processed into a component, the above characteristics are inherited, and thus an effect equivalent to that of the steel sheet of this embodiment can be obtained.
[0268] When measuring the component, it is preferable to measure a part with a relatively small amount of processing (a flat part, for example, a curvature radius R of 1000 mm or more). In addition, it is preferable to measure a part that avoids the spot welding area and the like.
[0269] <Manufacturing method>
[0270] The steel sheet of this embodiment can be manufactured by a manufacturing method including the following steps (I) to (V). In addition, unless otherwise specified, the temperature described below refers to the surface temperature of the steel sheet or the slab.
[0271] (I) Hot rolling process: Heat a slab having the same chemical composition as the above steel sheet, and in the first finishing mill stand, perform hot rolling starting at an average temperature of 850 °C or less from the surface to 10% of the thickness, thereby obtaining a hot-rolled steel sheet.
[0272] (II) Coiling process: After the hot rolling process, coil the hot-rolled steel sheet at a coiling temperature of 550 - 450 °C.
[0273] (III) Holding process: After the coiling process, hold the hot-rolled steel sheet with a holding time at a temperature higher than the coiling temperature and in the range of 650 - 500 °C for 1 hour or more.
[0274] (IV) Cold rolling process: After the holding process, perform cold rolling on the hot-rolled steel sheet under the conditions that the sheet thickness reduction rate is 20 - 80% and the average dynamic friction coefficient of the final two passes is 0.025 or more, thereby obtaining a cold-rolled steel sheet.
[0275] (V) Annealing process, which is carried out after the cold rolling process, and the cold rolled steel sheet is annealed by maintaining it for 60 seconds or more in the temperature range of 740 - 900 °C in an atmosphere with a dew point of -30 to 20 °C.
[0276] The following will explain each process.
[0277] [Hot rolling process]
[0278] In the hot rolling process, a slab having the same chemical composition as the steel sheet of the present embodiment described above is heated and hot rolled to produce a hot rolled steel sheet. The slab heating conditions in hot rolling are not limited, and it is preferably heated to 1100 °C or higher. When the heating temperature is lower than 1100 °C, the homogenization of the material is likely to become insufficient.
[0279] In finish rolling, regarding the inlet side temperature of the first finish rolling stand (the stand for the first pass of finish rolling), the average temperature from the surface to 10% of the thickness is set to 850 °C or lower. On the inlet side of the first finish rolling stand, by setting the average temperature from the surface to 10% of the thickness to 850 °C or lower, fine and soft ferrite with an average grain size of 5 μm or less can be formed on the surface layer of the steel sheet during the coiling process starting from the cooling after rolling. By forming such a structure, the shear strain of cold rolling can be preferentially accumulated near the surface layer in the subsequent cold rolling process.
[0280] The temperature of the steel sheet is measured before finish rolling, and simulation is carried out based on the obtained temperature, whereby the average temperature from the surface to 10% of the thickness can be estimated. In addition, if the temperature gradient of the steel sheet is small and the temperature in the region exceeding 10% of the plate thickness becomes 850 °C or lower, the rolling load will increase and finish rolling cannot be carried out. Therefore, in order to impart an appropriate temperature gradient in the plate thickness direction, water cooling can also be carried out in such a way that only the surface layer is cooled before the start of finish rolling.
[0281] The manufacturing method of the slab is not limited. From the viewpoint of productivity, it is preferably cast by the continuous casting method, but it can also be manufactured by the ingot casting method or the thin slab casting method.
[0282] When the steel billet obtained by continuous casting can be directly supplied to the hot rolling process at a sufficiently high temperature, the heating of the slab can also be omitted.
[0283] [Coiling process]
[0284] In the coiling process, the steel sheet after the hot rolling process (hot rolled steel sheet) is coiled at a coiling temperature of 550 - 450 °C. After hot rolling, the cooling conditions to the coiling temperature are not particularly limited.
[0285] By coiling at a coiling temperature of 550 to 450 °C, fine ferrite can be formed on the surface layer of the steel plate. If the coiling temperature is too low, fracture may occur during cold rolling, so the coiling temperature is preferably set at 450 °C or higher.
[0286] [Holding process]
[0287] In the holding process, the holding time at 650 to 500 °C, which is higher than the coiling temperature, is set to 1 hour or more to hold the coiled steel plate (hot-rolled steel plate). The holding time can also be set to 6 hours or less. The holding method in such a temperature range is not limited. For example, the coil can be inserted into a soaking furnace maintained at this temperature. Since it deteriorates pickling properties, usually, holding for more than 1 hour is not performed in this temperature range.
[0288] By holding with the holding time at 650 to 500 °C set to 1 hour or more, fine ferrite can be formed on the surface layer of the steel plate. By forming such a structure, it is possible to preferentially accumulate the shear strain of cold rolling near the surface layer in the subsequent cold rolling process. In addition, during the heating of the annealing process, recrystallization of the ferrite in the strain accumulation part on the surface layer is fully carried out, and unrecrystallized ferrite, which is the cause of bend anisotropy, can be reduced. In addition, since the shear strain of cold rolling is preferentially accumulated near the surface layer, the generated recrystallized ferrite can be significantly made finer, and the aspect ratio of the hard phase generated during the cooling process after heating in the annealing process can be reduced. Furthermore, the texture of the surface soft part also becomes appropriate. That is, in the ferrite of the surface soft part, the Taylor factor M value M L of the L section and the Taylor factor M value M c of the C section, the ratio M L / M c is set to 0.95 or more.
[0289] [Cold rolling process]
[0290] In the cold rolling process, after removing the scale of the steel plate (hot-rolled steel plate) after the holding process by pickling or the like according to a known method as needed, cold rolling is carried out under the conditions that the sheet thickness reduction rate is 20% to 80% and the average dynamic friction coefficient of the final two passes is 0.025 or more, thereby producing a cold-rolled steel plate.
[0291] By carrying out cold rolling under the conditions that the sheet thickness reduction rate is 20% to 80% and the average dynamic friction coefficient of the final two passes is 0.025 or more, strain can be concentratedly accumulated on the surface layer of the steel plate. During the heating of the annealing process, recrystallization of the fine ferrite structure on the surface layer is fully carried out, and unrecrystallized ferrite, which is the cause of increasing bend anisotropy, can be reduced. As a result, M L / M cClose to 1. In addition, it is possible to reduce the aspect ratio of the hard phase generated during the cooling process after heating in the annealing process. Moreover, the texture of the surface layer also becomes appropriate. That is, M L / M c is set to 0.95 or more.
[0292] The average dynamic friction coefficient in the final two passes is set to 0.035 or more, and more preferably set to 0.055 or more.
[0293] When the sheet thickness reduction rate is set with the sheet thickness before cold rolling as t0 and the sheet thickness after cold rolling as t1, it can be expressed as (1 - t1 / t0) × 100 (%). In addition, the average dynamic friction coefficient in the final two passes is obtained using the measured rolling load, adopting the dynamic average deformation resistance formula of Gohara-Kihara, the roll elastic flattening equation of Hitchcock, and the cold rolling theory formula of Bland and Ford.
[0294] After the cold rolling process, the cold rolled steel sheet can also be subjected to treatments such as degreasing according to known methods as needed.
[0295] [Annealing process]
[0296] In the annealing process, the steel sheet after the cold rolling process (cold rolled steel sheet) is annealed by being held for 60 seconds or more in an atmosphere with a dew point of -30°C to 20°C in a temperature range of 740°C to 900°C. The holding time in the temperature range of 740 to 900°C can also be set to 400 seconds or less. For the heating and holding in the subsequent annealing process, in order to form a desired structure in the surface soft part and the 1 / 4 depth position, the cold rolled steel sheet can be cooled, held, quenched, and tempered. In addition, hot dip galvanizing and alloying can also be carried out.
[0297] Starting from the temperature rise in the annealing process, by setting the atmosphere during heating as described above, decarburization of the steel sheet surface layer during annealing can be carried out, and ferrite formation can be promoted on the steel sheet surface layer during the highest heating temperature and subsequent cooling. As a result, Hs / Hc can be set to 0.65 or less. In addition, in this way, the metal structure of the surface soft part can be set to: ferrite is 50% or more, and the total of one or two or more of quenched martensite, pearlite, and retained austenite is 0% to 50%.
[0298] The holding time of the annealing temperature is preferably 60 seconds or more. If the holding time of the annealing temperature is less than 60 seconds, decarburization cannot be carried out sufficiently, and thus the ferrite fraction in the surface layer may not be 50% or more.
[0299] [Hot dip galvanizing]
[0300] [Alloying]
[0301] In the case of manufacturing cold-rolled steel sheets (hot-dip galvanized steel sheets) with a hot-dip galvanized layer on the surface, in the process of cooling after annealing (annealing and cooling process), hot-dip galvanization can also be carried out by immersing the steel sheet in a plating bath at the same temperature in a state where the surface temperature of the steel sheet exceeds 425 °C and is lower than 600 °C. In addition, in the case of manufacturing cold-rolled steel sheets (alloyed hot-dip galvanized steel sheets) with an alloyed hot-dip galvanized layer on the surface, an alloying heat treatment, for example, heating to a temperature exceeding 450 °C and lower than 600 °C, can be carried out after the hot-dip galvanization process, so that the coating becomes an alloyed hot-dip galvanized layer.
[0302] [Tempering process]
[0303] The cold-rolled steel sheet after the annealing process is cooled to a temperature range of 50 °C to 250 °C at a cooling rate of 30 °C / second or more, whereby the austenite that has not undergone a phase change is transformed into martensite.
[0304] In the tempering process, by tempering the cold-rolled steel sheet at 200 to 350 °C for 1 second or more, a structure mainly composed of martensite (tempered martensite) can be stably obtained at the 1 / 4 depth position.
[0305] In addition, the tempering process is not an essential process.
[0306] In the case where the hot-dip galvanization process and / or the alloying process has been carried out, the cold-rolled steel sheet after the hot-dip galvanization process or the cold-rolled steel sheet after the hot-dip galvanization process and the alloying process is cooled to a temperature range of 50 °C to 250 °C, and then tempered at a temperature of 200 °C to 350 °C for 1 second or more. If the tempering temperature exceeds 350 °C, the strength of the steel sheet decreases. Therefore, the tempering temperature is set to 350 °C or lower. The tempering temperature is preferably 325 °C or lower, more preferably 300 °C or lower. On the other hand, if the tempering temperature is lower than 200 °C, the tempering is insufficient, and the bendability and hydrogen embrittlement resistance characteristics deteriorate. Therefore, the tempering temperature is set to 200 °C or higher. The tempering temperature is preferably 220 °C or higher, more preferably 250 °C or higher.
[0307] The tempering time can be 1 second or more, but for stable tempering treatment, it is preferably 5 seconds or more, and more preferably 10 seconds or more. On the other hand, long-term tempering sometimes reduces the strength of the steel sheet, so the tempering time is preferably 750 seconds or less, and more preferably 500 seconds or less.
[0308] [Skin pass rolling process]
[0309] The cold-rolled steel sheet after the tempering process can also be skin-passed after being cooled to a temperature at which skin-passing can be performed. When the cooling after annealing is water spray cooling using water, immersion cooling, air-water cooling, etc., in order to remove the oxide film formed by contact with water at high temperature and improve the chemical conversion treatment property of the steel sheet, it is preferable to perform pickling and plating of one or more of trace amounts of Ni, Fe, Co, Sn, and Cu after pickling before skin-passing. Here, trace amount means a plating amount of about 3 to 30 mg / m on the surface of the steel sheet. 2 or so.
[0310] By skin-passing, the shape of the steel sheet can be adjusted. The draw ratio of skin-passing is preferably 0.05% or more. More preferably, it is 0.10% or more. On the other hand, if the draw ratio of skin-passing is high, the area ratio of retained austenite decreases and the ductility deteriorates. Therefore, the draw ratio is preferably set to 1.00% or less. The draw ratio is more preferably 0.75% or less, and further preferably 0.50% or less.
[0311] Examples
[0312] The present invention will be described more specifically with reference to the examples. The conditions of the examples are one set of conditional examples adopted to confirm the feasibility of implementing the present invention and the effects, and the present invention is not limited to this one set of conditional examples. The present invention can adopt various conditions without departing from the gist of the present invention and achieving the purpose of the present invention.
[0313] Slabs having the chemical compositions shown in Table 1A and Table 1B are cast. The cast slabs are hot-rolled under the conditions of Table 2A and Table 2B. After rolling, coiling and holding are performed under the conditions of Table 2A and Table 2B. After holding, cold rolling is performed under the conditions of Table 2A and Table 2B to produce a cold-rolled steel sheet with a thickness of 1 mm to 2 mm, and then annealing is performed under the conditions of Table 3A and Table 3B. In addition, the cold-rolled steel sheet after the annealing process is cooled to a temperature range of 50°C to 250°C at a cooling rate of 30°C / second or more.
[0314] In addition, for the examples described as "with plating" in "presence or absence of plating", hot-dip galvanizing is performed by immersing in a plating bath at the same temperature in a state where the surface temperature of the steel sheet exceeds 425°C and is lower than 600°C. Furthermore, for the examples described as "with alloying" in "presence or absence of alloying", an alloying heat treatment is performed by heating to exceed 450°C and be lower than 600°C.
[0315]
[0316]
[0317]
[0318]
[0319] Table 3A
[0320]
[0321] Table 3B
[0322]
[0323] The underlines indicate outside the scope of the present invention
[0324] By the above method, the metallographic structure at the 1 / 4 depth position and the metallographic structure of the surface soft part were evaluated from the obtained cold-rolled steel sheet. In addition, since the rolling direction of the steel sheet was determined from the manufacturing process, the rolling direction was not discriminated
[0325] In addition, according to the procedure shown below, the tensile strength (TS), the ultimate bending angle (C-axis bending angle) θ C and the anisotropy of the ultimate bending angle were evaluated
[0326] The tensile strength (TS) was obtained by taking a JIS No. 5 tensile test piece in a direction perpendicular to the rolling direction from the cold-rolled steel sheet and performing a tensile test in accordance with JIS Z 2241:2022. When the tensile strength is 1180 MPa or more, the steel sheet is judged to have a high strength
[0327] The ultimate bending angle was obtained by the above bending test in accordance with VDA (German Automobile Industry Association Standard) 238-100. When the tensile strength is 1180 to 1470 MPa, the case where the ultimate bending angle θ C is 90° or more was judged as qualified. When the tensile strength exceeds 1470 MPa, the case where the ultimate bending angle θ C is 80° or more was judged as qualified. When the above conditions are not satisfied, it is judged that the bendability is poor and judged as unqualified
[0328] In this embodiment, as described above, the judgment criterion for changing the ultimate bending angle θ C depending on the tensile strength is based on the following background. If the tensile strength is low, the absolute value of the ultimate bending angle increases. For example, in the cases of No. 21 and No. 24, the absolute value of the ultimate bending angle reaches a level not inferior to that of the steel materials of the invention examples. However, the ultimate bending angles of No. 21 and No. 24 only increase because they are steel materials with relatively low tensile strengths. In other words, if Hs / Hc, which is a feature of the present application, is satisfied under the same chemical composition and tensile strength as No. 21 and No. 24, there is a possibility of obtaining a steel sheet with a further increased ultimate bending angle
[0329] The ultimate bending angle θ in the direction along the rolling direction L and the ultimate bending angle θ in the direction perpendicular to the rolling direction and the plate thickness direction C The ratio θ L / θ C When it exceeds 0.80, it is judged that the bending anisotropy is excellent and judged as qualified (OK). On the other hand, when θ L / θ C is 0.80 or less, it is judged that the bending anisotropy is poor and judged as unqualified (NG). The obtained results are shown in Tables 5A and 5B.
[0330] As can be seen from Tables 5A and 5B, the bendability of the examples of the present invention is excellent and the bending anisotropy is small.
[0331]
[0332]
[0333] Table 5A
[0334]
[0335] Table 5B
[0336]
[0337] The underlines indicate outside the scope of the present invention
[0338] Industrial applicability
[0339] According to the above solution of the present invention, it is possible to provide a steel sheet with excellent bendability and small bending anisotropy and a method for manufacturing the steel sheet.
Claims
1. A steel plate, wherein, the chemical composition of the steel plate contains by mass%: C: 0.09 - 0.25%, Si: 0.01 - 2.00%, Mn: 1.5 - 3.5%, P: 0.100% or less, S: 0.0500% or less, N: 0.0100% or less, O: 0.0060% or less, Al:0~1.000%、 Cr:0~2.000%、 Mo: 0 - 1.000%, W:0~1.000%、 Co: 0 - 0.500%, B:0~0.0100%、 Nb: 0 - 0.50%, Ti: 0 - 0.5000%, V:0~0.500%、 Ta: 0 - 0.100%, Sn: 0 - 0.050%, Sb: 0 - 0.050%, As: 0 - 0.050%, Ni: 0 - 1.000%, Cu: 0 - 1.000%, Ca: 0 - 0.050%, Zr:0~0.050%、 Mg: 0 - 0.050%, and REM: 0 - 0.100%, the balance consists of Fe and impurities; in the metallographic structure at a position 1 / 4 of the plate thickness from the surface along the plate thickness direction, i.e., at the 1 / 4 depth position, by area ratio, the total of ferrite and bainite is 0 - 40%, martensite is 50 - 100%, the total of pearlite and retained austenite is 0 - 10%; in the metallographic structure in the region from the surface to 20 μm along the plate thickness direction, i.e., in the surface soft part, by area ratio, ferrite is 50% or more, the total of one or more of martensite, bainite, pearlite, and retained austenite is 0 - 50%, the ratio Hs / Hc of the Vickers hardness Hs of the surface soft part to the Vickers hardness Hc of the 1 / 4 depth position is 0.65 or less, In the ferrite of the surface soft part, the Taylor factor M value M of the L section L and the Taylor factor M value M of the C section c The ratio M L / M c is 0.95 or more. the aspect ratio of the island - shaped hard phase in the surface soft part is 3.0 or less and the major axis is 5.0 μm or less.
2. The steel plate according to claim 1, wherein, The ultimate bending angle θ in the direction along the rolling direction L and the ultimate bending angle θ in the direction perpendicular to the rolling direction and the plate thickness direction C The ratio θ L / θ C exceeds 0.
80.
3. The steel plate according to claim 1 or 2, wherein The tensile strength is 1180 MPa or more.
4. The steel plate according to claim 2, wherein, When the tensile strength is 1180 to 1470 MPa, the ultimate bending angle θ C is 90° or more. When the tensile strength exceeds 1470 MPa, the ultimate bending angle θ C is 80° or more.
5. The steel plate according to claim 1 or 2, wherein, the plate thickness is 1.0 mm or more.
6. The steel plate according to claim 1 or 2, wherein, The chemical composition contains by mass% Al:0.001~1.000%、 Cr:0.001~2.000%、 Mo: 0.010 - 1.000%, W:0.001~1.000%、 Co: 0.010 - 0.500%, B:0.0001~0.0100%、 Nb: 0.01 - 0.50%, Ti: 0.0001 - 0.5000%, V:0.001~0.500%、 Ta: 0.001 - 0.100%, Sn: 0.001 - 0.050%, Sb: 0.001 - 0.050%, As: 0.001 - 0.050%, Ni: 0.010 - 1.000%, Cu: 0.001 - 1.000%, Ca: 0.001 - 0.050%, Zr:0.001~0.050%、 Mg: 0.0001 - 0.050%, and REM: one or more of 0.001 - 0.100%.
7. The steel plate according to claim 1 or 2, wherein There is a hot - dip galvanized layer on the surface.
8. The steel plate according to claim 1 or 2, wherein, There is an alloyed hot - dip galvanized layer on the surface.
9. A method for manufacturing a steel plate, wherein, The manufacturing method includes: a hot - rolling process, which heats the slab and then performs hot - rolling starting with finishing rolling under the condition that the average temperature from the surface to 10% of the thickness is 850°C or less in the first finishing mill stand to obtain a hot - rolled steel plate, and the chemical composition of the slab contains by mass%: C:0.09~0.25%、 Si: 0.01 - 2.00%, Mn: 1.5 - 3.5%, P: 0.100% or less, S: 0.0500% or less, N: 0.0100% or less, O: 0.0060% or less, Al:0~1.000%、 Cr:0~2.000%、 Mo: 0 to 1.000%, W:0~1.000%、 Co: 0 to 0.500%, B:0~0.0100%、 Nb: 0 to 0.50%, Ti: 0 to 0.5000%, V:0~0.500%、 Ta: 0 to 0.100%, Sn: 0 to 0.050%, Sb: 0 to 0.050%, As: 0 to 0.050%, Ni: 0 to 1.000%, Cu: 0 to 1.000%, Ca: 0 to 0.050%, Zr:0~0.050%、 Mg: 0 to 0.050%, and REM: 0 to 0.100%, the balance consists of Fe and impurities; a coiling step of coiling the hot-rolled steel sheet at a coiling temperature of 550 to 450°C after the hot-rolling step; a holding step of holding the hot-rolled steel sheet for 1 hour or more at a holding temperature higher than the coiling temperature and within the range of 650 to 500°C after the coiling step; a cold-rolling step of cold-rolling the hot-rolled steel sheet under the conditions that the sheet thickness reduction rate is 20 to 80% and the average dynamic friction coefficient in the final two passes is 0.025 or more after the holding step, thereby obtaining a cold-rolled steel sheet; and an annealing step of annealing the cold-rolled steel sheet in an atmosphere with a dew point of -30 to 20°C and holding for 60 seconds or more in a temperature range of 740 to 900°C after the cold-rolling step.
Citation Information
Patent Citations
High strength cold rolled steel sheet and method for producing the same
JP2015145521A
High-strength steel sheet
WO2020196060A1